2022
DOI: 10.1021/jacs.1c12644
|View full text |Cite
|
Sign up to set email alerts
|

Destabilized Carbocations Caged in Water Microdroplets: Isolation and Real-Time Detection of α-Carbonyl Cation Intermediates

Abstract: Over the last 50 years, proposals of α-carbonyl cation intermediates have been driven by chemical intuition and indirect evidence. Recently, wide interest in α-carbonyl cation chemistry has opened new gates to prepare α-functionalized carbonyl compounds. Though these intrinsically unstable carbocations are formed under forcing conditions (e.g., in a strong acid medium), their fleeting existence prohibits direct observation or spectroscopic measurement. We report that high-speed aqueous microdroplets can direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…Researches from our group and others have shown that water microdroplets exhibit unusual reaction properties that are not observed in bulk water or other organic solvents. One possible reason for the unique properties of water microdroplets is the large amount of hydroxyl radicals at the water–gas interface produced by a strong electric field and by contact electrification . Taking advantage of this feature, our group and others have shown that hydrogen peroxide forms in water microdroplets. The hydrogen peroxide originates from the recombination of two hydroxyl radicals at the surface of the water microdroplet.…”
mentioning
confidence: 91%
“…Researches from our group and others have shown that water microdroplets exhibit unusual reaction properties that are not observed in bulk water or other organic solvents. One possible reason for the unique properties of water microdroplets is the large amount of hydroxyl radicals at the water–gas interface produced by a strong electric field and by contact electrification . Taking advantage of this feature, our group and others have shown that hydrogen peroxide forms in water microdroplets. The hydrogen peroxide originates from the recombination of two hydroxyl radicals at the surface of the water microdroplet.…”
mentioning
confidence: 91%
“…The capture and monitoring of activated radical cations are challenging and interesting topics owing to the high reactivity and poor thermodynamic stability of these cations. Furthermore, carbocation intermediates normally exist under harsh conditions (such as in the presence of high-energy UV irradiation, strong Lewis/Brønsted acids, solvolysis, and high temperatures), 7,8 which makes real-time characterization difficult. Beyond instantaneous molecular information, the continuous monitoring of dynamic changes or transformations of different reactive intermediates (radical cations and carbocations) would also offer signicant benets to in-depth SET studies.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] In the past decade or so, tertiary α-hydroxy ketones have also been utilized as versatile building blocks to access biologically active scaffolds of heterocycles and α-functionalized ketones. [34][35][36][37][38][39][40] Analyses of the existence of conformational preferences (if any) among tertiary α-hydroxy ketone moieties may show some light on their mode of action (based on molecular topology) that leads to biological activity.…”
Section: Introductionmentioning
confidence: 99%